In search of Paul : how Jesus's Apostle opposed Rome's empire with God's kingdom : a new vision of Paul's words & world /: how Jesus's Apostle opposed Rome's empire with God's kingdom : a new vision of Paul's words & world. (2009) - Unknown
No abstract available